Microbubble-mediated sonoporation for highly efficient transfection of recalcitrant human B-cell lines - Yong, Charlene Li Ling (2015)
Sonoporation has not been widely explored as a strategy for the transfection of heterologous genes into notoriously difficult-to-transfect mammalian cell lines such as B cells. This technology utilizes ultrasound to create transient pores in the cell membrane, thus allowing the uptake of extraneous DNA into eukaryotic and prokaryotic cells, which is further enhanced by cationic microbubbles. This study investigates the use of sonoporation to deliver a plasmid encoding green fluorescent protein (GFP) into three human B-cell lines (Ramos, Raji, Daudi). A higher transfection efficiency (TE) of >42% was achieved using sonoporation compared with <3% TE using the conventional lipofectamine method for Ramos cells. Upon further antibiotic selection of the transfected population for two weeks, we successfully enriched a stable population of GFP-positive Ramos cells (>70%). Using the same strategy, Raji and Daudi B cells were also successfully transfected and enriched to 67 and 99% GFP-positive cells, respectively. Here, we present sonoporation as a feasible non-viral strategy for stable and highly efficient heterologous transfection of recalcitrant B-cell lines. This is the first demonstration of a non-viral method yielding transfection efficiencies significantly higher (42%) than the best reported values of electroporation (30%) for Ramos B-cell lines.